Spatiotemporal Variations in Phytoplankton Community Structure and Diversity: A Case Study for a Macroalgae–Oyster Reef Ecosystem - Min Xu; Qi Zhao; Yufu Xu; Shenzhi Wang; Yingbo Yu; Haipeng Zhang; Yun Wang; Jiabin Shen; Linlin Yang; Yunling Zhang; Takayoshi Otaki; Teruhisa Komatsu; et al. (Diversity)
The estuarine area of Luanhe River is an important fisheries ground in China’s Bohai Sea. In 2016, Tangshan Marine Ranching Co., Ltd. constructed a 2 km2 artificial oyster–macroalgae reef area by placing artificial reefs on the seabed adjacent to the Luanhe River Estuary. This action resulted in sustainable annual economic outputs through the fishing and sea cucumber put-and-take fishery. Although Luanhe River runoff and reef construction are important to the local phytoplankton community and fisheries’ production, little is known about how these factors affect phytoplankton community structure in the local coastal ecosystem. In this study, we conducted field surveys to investigate the spatiotemporal variations in species composition, abundance, dominant species, diversity indexes, niche width and overlap, and interspecific connection of the phytoplankton community in the ecosystem of oyster–macroalgal reefs. From July 2016 to August 2017, we collected data before and after reef construction in areas inside and outside of the benthic reefs in both the flood and dry seasons of Luanhe River runoff. We found a total of 79 species, with the majority represented by diatoms and dinoflagellates. The dominant species were Paralia sulcata and Coscinodiscus sp. The total species number and abundance increased from May to September. The species number in the reef area was greater than that outside the reef. Species abundance from August to September was greater in the reef area than in the control area, which was opposite the situation from May to June. We found more phytoplankton abundance in the flood season compared with that in the dry season. Our results suggest that reef construction can benefit the local phytoplankton community and that further studies of the relationship among oysters, macroalgae, and phytoplankton in the system are warranted. Moreover, we provide baseline data about variations in the phytoplankton community in a sea ranch area.